SINTESIS DAN KARAKTERISASI NPP PERAK (Ag-NPs) MENGGUNAKAN EKSTRAK KULIT BUAH NAGA SEBAGAI BIOREDUKTOR - Rosman Parningotan; Yanuar Hamzah (Komunikasi Fisika Indonesia, 2020)
Silver nanoparticle were successfully synthesized by using the red dragon fruit peel extract as a bioreductor. The synthesis process is mixed the solution of silver nitrate (AgNO3) 1mM and red dragon fruit peel extract with a volume ratio 1 : 5 and and then mixed with a few drops of NaOH solution 1M until the solution has a pH of 10 each and then stirred using magnetic stirrer for 14 minutes for each sample then incubator. The sample are characterized using the Ultra Violet Visible (UV-Vis) spectroscopy resulting in the wavelength peaks and energy band gap at 416 nm and 2.98 eV. A functional group that plays a role in reducting AgNO3 using the Fourier Transform Infra-Red Spectroscopy (FTIR) show six major groups that have interval of 602–3427 cm-1. The result of the X-Ray Diffraction (XRD) spectrum analysis saw a 10.07–102.73 nm crystal size with the Face Center Cubic (FCC) crystalline structure and have an Ag2O impurity. From Scanning Electron Microscope (SEM) image shows that morphology of sample is still agglomerated. The findings of the present research lead to conclusion that the red dragon fruit peel was found to reduced the silver ions to silver nanoparticle.